"Let Us Worship" or Let Us "Breathe": Sean Feucht and Maverick City Music's Divergent Approaches to Worship and Politics - Lucas, Karen Hamilton (Pneuma, 2026)
During the social and political upheaval in the United States in 2020-2021, praise and worship leaders, Sean Feucht and Maverick City Music, both used singing for political engagement but took markedly different approaches. Given a shared Pentecostal-Charismatic heritage, their theological perspectives were similar, but their social concerns differed sharply. Feucht's #LetUsWorship movement protested COVID-19 restrictions, framed Christians as victims of government overreach, and endorsed Donald Trump. In contrast, Maverick City Music addressed concerns about racial injustice and encouraged Christian unity in diversity. Though both groups view singing as a weapon for spiritual warfare, their strategies and priorities highlight divergent views about spiritual realities beneath the nation’s political concerns, particularly along racial lines.